Analysis Of Factors Affecting Accounting Students' Interest In Pursuing A Career As A Public Accountant - Penola, Yola; Wagini, Wagini; Harwini, Dewi (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
The purpose of this study was to analyze the factors that influence accounting students’ interest in pursuing a career as a public accountant at Dehasen University, Bengkulu. The study specifically examined the effects of three independent variables—financial rewards, work environment, and professional recognition—on students’ career interest. A quantitative research method with a multiple linear regression approach was employed. The data were obtained from 100 active accounting students from the 2022–2024 cohorts, selected using probability sampling based on the Slovin formula. The data collection instrument was a structured questionnaire that had been tested for validity and reliability. Statistical analysis was conducted using SPSS version 23, including tests of validity, reliability, classical assumptions, and hypothesis testing through t-tests and F-tests to determine both partial and simultaneous effects of the independent variables. The results showed that financial rewards, work environment, and professional recognition each had a positive and significant influence on accounting students’ interest in becoming public accountants. Among these factors, professional recognition emerged as the most dominant variable affecting students’ interest. Simultaneously, all three variables significantly influenced career interest, as indicated by an F-value of 21.268 with a significance level of 0.000. The coefficient of determination (R²) was 0.399, meaning that 39.9% of students’ career interest could be explained by the three factors, while the remaining 60.1% was influenced by other variables not examined in this study. These findings suggest that universities should enhance academic activities that promote student professionalism, while public accounting firms should provide supportive work environments and fair compensation to attract future professionals in the accounting field.